2014
DOI: 10.1016/j.pcd.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity is an independent risk indicator when estimating diabetes risk with FINDRISC scores: A cross sectional study comparing immigrants from the Middle East and native Swedes

Abstract: Our study suggests that Middle Eastern ethnicity should be considered an independent risk indicator for diabetes. Accordingly, the implementation of culturally tailored prevention programs may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 24 publications
5
85
1
2
Order By: Relevance
“…Differences in comparison to our survey could be attributable to differences in the sizes of the investigated populations (1398 vs 123 non-European immigrants), but also to the fact that the results of Wändell et al were collected between 1997 and 1999, more than a decade earlier than our present results. Previously, in the MEDIM study, we showed that, of the Iraqi immigrants to Sweden who had not yet developed diabetes, a large proportion were expected to do so within the next decade [6]. Thus, our present data are likely to reflect a growing diabetes prevalence in this non-European immigrant population.…”
Section: Diabetes Onsetsupporting
confidence: 54%
“…Differences in comparison to our survey could be attributable to differences in the sizes of the investigated populations (1398 vs 123 non-European immigrants), but also to the fact that the results of Wändell et al were collected between 1997 and 1999, more than a decade earlier than our present results. Previously, in the MEDIM study, we showed that, of the Iraqi immigrants to Sweden who had not yet developed diabetes, a large proportion were expected to do so within the next decade [6]. Thus, our present data are likely to reflect a growing diabetes prevalence in this non-European immigrant population.…”
Section: Diabetes Onsetsupporting
confidence: 54%
“…A summarizing sketch of the final Directed Acyclic Graph is displayed in figure 2. 19 According to figure 2, age, sex and country of origin should always be adjusted for when studying an association between any of the exposures and the outcome. Age, sex and country of origin precede the exposures and are potentially associated with both the exposures and the outcome.…”
Section: Methodsmentioning
confidence: 99%
“…16 Several Swedish studies have shown that immigrants have increased risk for diabetes and diabetes complications. [17][18][19][20] In this paper we study education, income and immigration as risk factors for high HbA1c when diagnosed with T2D or LADA.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…The baseline study included a randomly selected sample of Iraqi-born and Swedish-born residents matched for age and sex (19) . The information collected during the baseline study was used to select participants for the intervention study.…”
Section: Study Participantsmentioning
confidence: 99%
“…Results from the MEDIM study ('the impact of Migration and Ethnicity on Diabetes in Malmö') have shown that Iraqi immigrants have a higher prevalence of T2D (11·6 v. 5·8 %, P < 0·001) compared with native Swedes. They also exhibit a clustering of T2D risk factors such as obesity (37·5 v. 23·0 %, P < 0·001), physical inactivity (71·9 v. 38·6 %, P < 0·001) and a positive family history of diabetes (51·7 v. 27·6 %, P < 0·001) compared with ethnic Swedes living in Malmö (19) . A culturally adapted lifestyle intervention, including modification of both dietary and PA habits, was successful in reducing body weight and LDL cholesterol and improving insulin sensitivity in Iraqi immigrants from MEDIM (20) .…”
mentioning
confidence: 96%